P165 Latent tuberculosis infections (ltbi) national screening programme. (15th November 2017) - Abunga, YO; Day, M; Wright, N; Brij, SO
Abstract : Background: The new entrant TB screening programme identified very few persons for Latent TB screening locally. However, following national funding for community LTBI screening, 12 GP practices were identified to undertake IGRA testing in "high risk" registered persons. Aims: To evaluate the feasibility and clinical outcomes of the LTBI National Screening Programme Methods: From May 2016 until April 2017, persons from countries with high TB incidence (≥150/100, 000 population) and sub-Saharan Africa were identified by the GP practices and offered LTBI screening with IGRA if they had arrived in the UK in the last 5 years and were aged 16–35 years. IGRA Results were forwarded to the TB team at the local hospital. Persons with positive, borderline positive and indeterminate Results were offered appointments for assessment and treatment in the TB Clinic. Results: 360 persons were community-screened for LTBI. Of the 360 persons, 305 (84.7%) had non-reactive IGRA Results and therefore did not require follow up. The remaining 55 (15.3%) had either positive, borderline positive or 2 indeterminate Results and were referred to the local TB team. Of 55 persons referred 2 did not attend any appointments offered and 53 attended 2 of whom were subsequently found to have active TB. The treatment completion rate was 89.2% (see Table 1 ). Despite the inclusion criteria, of the 55 persons offered consultation, 16 had been residing in the UK for more than 5 years and 7 were over the age of 35. Conclusion: Retrospective case-finding in General Pracice is feasible and the uptake for screening appeared very successful. Inclusion criteria were not strictly adhered to but identified persons with LTBI were offered non-funded treatment. Treatment completion rates were excellent. These Results will hopefully inspire on-going prospective screening of newly registered persons and prove to be more successful in the long-term than new entrant screening.